Data Privacy and the Law: Balancing Security and Individual Rights - Amaliasyifa Agustina; Mutiara Oktavia Cahyania; Muhammad Syaoqibihillah (Law Studies and Justice Journal (LAJU), 2024)
Data privacy regulations are undergoing significant changes in the face of challenges presented by technological advances, particularly in the context of artificial intelligence (AI) and the Internet of Things (IoT). This study describes the evolution of data privacy regulations, the challenges in adapting regulations to AI and IoT, and the implementation of data privacy regulations related to AI and IoT. In conducting this research, researchers used a systematic literature review method to identify and analyze the latest articles in relevant literature. The findings of this study show that efforts to adapt data privacy regulations to developments in new technologies such as AI and IoT introduce new complexities that demand innovative solutions. Nonetheless, this research highlights the potential of solutions such as Federated Learning (FL) and Blockchain integration with IoT in improving data security and privacy. The implications of this research include the importance of paying attention to flexible and adaptable regulations, as well as the need for collaborative efforts in facing increasingly complex data privacy challenges in the era of AI and IoT.